BUSINESS SUCCESS INFLUENCED BY CREATIVITY, ENTREPRENEURIAL KNOWLEDGE AND BUSINESS CAPITAL - Prabowo, Catur; Tasriastuti, Nurrohmi Ambar; Pelupessy, Ig. Henri; Harminingtyas, Rudika; Fahlefi, Diva Riza (STIE Pelita Nusantara Semarang, 2024)
The purpose of this study was to determine the effect of creativity, entrepreneurial knowledge and business capital on business success (Case study on MSMEs in West Semarang District). The population in this study was 50 MSME actors. Data collection techniques used observation, case studies and questionnaires. Data analysis techniques used quantitative methods. In this study, the method used to analyze data was the Partial Least Square (PLS) method using SmartPLS 3.0 software. The results of the test study showed a positive and significant effect on the creativity variable (X1) on business success (Y1) with an effect size of 0.161 which is categorized as medium. There is a positive and significant effect on the entrepreneurial knowledge variable (X2) on business success (Y1) with an effect size of 0.108 which is categorized as medium. There is a positive and significant effect on the business capital variable (X3) on business success (Y1) with an effect size of 0.577 which is categorized as large. The implications of this study are that creativity, entrepreneurial knowledge and business capital have a very important role in the success of MSMEs in West Semarang District. MSMEs need to increase innovation in developing products, broaden their entrepreneurial insights and also manage their capital well to increase business success